Seasonally and Spatially Variable Organic Matter Contributions From Watershed, Marine Macrophyte, and Pelagic Sources to the Northeast Pacific Coastal Ocean Margin - St. Pierre, Kyra A.; Hunt, Brian P. V.; Giesbrecht, Ian J. W.; Tank, Suzanne E.; Lertzman, Ken P.; Del Bel Belluz, Justin; Hessing-Lewis, Margot L.; Olson, Angeleen; Froese, Tyrel (Frontiers in Marine Science, 2022)
Globally, coastal waters are considered biogeochemical hotspots because they receive, transform, and integrate materials and waters from both land and the open ocean. Extending from northern California to southeast Alaska, the Northeast Pacific Coastal Temperate Rainforest (NPCTR) region is no exception to this, and hosts a diversity of watershed types (old-growth rainforest, bog forest, glaciers), and tidal (sheltered, exposed) and pelagic marine (deep fjord, shallow estuary, well-mixed channel) environments. With large freshwater fluxes to the coastal ocean, cross-ecosystem connectivity in the NPCTR is expected to be high, but seasonally variable, with pulses in runoff from rainfall, snowmelt and glacial melt, and primary production associated with changes in ocean upwelling and incident light. However, the relative contribution of each ecosystem to surface ocean organic matter pools over time and space remains poorly constrained, despite their importance for the structure and function of coastal marine ecosystems. Here, we use a four-year dataset of particulate organic matter (POM) chemical composition (δ13C, δ15N, C:N ratio) to quantify the relative contributions of watershed materials via riverine inputs, marine phytoplankton, and macrophytes (macroalgae and seagrass) to surface waters (0-10 m) at 11 stations representing fjord, shallow non-fjord estuary, sheltered channel and well-mixed coastal environments at the heart of the NPCTR in British Columbia, Canada. Watershed, marine phytoplankton, and macrophyte contributions to surficial POM ranged between 5-78%, 22-88%, and 0.1-18%, respectively, and varied by season and station. Watershed inputs were the primary source of POM across all stations in winter and were important throughout the year within the fjord. Marine phytoplankton were the principal source of POM in spring and at all stations outside of the fjord through summer and autumn, while macrophyte contributions were greatest in summer. These results demonstrated high, but seasonally and spatially variable, connectivity between ecosystems that are often considered in isolation of one another and highlight the need to consider coastal waters as integrated land-ocean meta-ecosystems. Future work should investigate how heterogeneity in POM sources determines its fate in coastal ecosystems,and the relative importance of different basal organic matter sources for the marine food web.